A Clinical Experimental Model to Evaluate Analgesic Effect of Remote Ischemic Preconditioning in Acute Postoperative Pain. (30th June 2016) - Pereira, Francisco Elano Carvalho; Mello, Irene Lopes; Pimenta, Fernando Heladio de Oliveira Medeiros; Costa, Debora Maia; Wong, Deysi Viviana Tenazoa; Fernandes, Claudia Regina; Lima Junior, Roberto César; Gomes, Josenília M. Alves
Abstract : This study aims to evaluate the viability of a clinical model of remote ischemic preconditioning (RIPC) and its analgesic effects. It is a prospective study with twenty (20) patients randomly divided into two groups: control group and RIPC group. The opioid analgesics consumption in the postoperative period, the presence of secondary mechanical hyperalgesia, the scores of postoperative pain by visual analog scale, and the plasma levels interleukins (IL-6) were evaluated. The tourniquet applying after spinal anesthetic block was safe, producing no pain for all patients in the tourniquet group. The total dose of morphine consumption in 24 hours was significantly lower in RIPC group than in the control group (p = 0.0156 ). The intensity analysis of rest pain, pain during coughing and pain in deep breathing, showed that visual analogue scale (VAS) scores were significantly lower in RIPC group compared to the control group:p = 0.0087, 0.0119, and 0.0015, respectively. There were no differences between groups in the analysis of presence or absence of mechanical hyperalgesia (p = 0.0704 ) and in the serum levels of IL-6 dosage over time (p < 0.0001 ). This clinical model of remote ischemic preconditioning promoted satisfactory analgesia in patients undergoing conventional cholecystectomy, without changing serum levels of IL-6.